2017
DOI: 10.1093/infdis/jix426
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines Produced in Response to Varicella-Zoster Virus Infection of ARPE-19 Cells Stimulate Lymphocyte Chemotaxis

Abstract: Posterior uveitis is an ocular complication that can occur with reactivation of varicella-zoster virus (VZV). It may lead to loss of vision due to retinal detachment and chronic inflammation, which often causes more severe disease than the virus infection itself. To increase our understanding of the immune response, we infected the retinal pigment epithelial (RPE) cell line, ARPE-19, with cell-associated VZV and compared its response to that of the MeWo cell line using multiplex assays. We observed (1) a diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Our findings showed that treatment with 0.2 ng/ml of IFN-␥ reduced intracellular VZV yields less than 2-fold compared to those of untreated cells. Since the levels of IFN-␥ in the supernatant were reduced by VZV infection in both ARPE-19 and MeWo cells compared to those of uninfected cells, and were less than 10 pg/ml (40), IFN-␥ produced in response to VZV infection is not sufficient to inhibit VZV replication.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Our findings showed that treatment with 0.2 ng/ml of IFN-␥ reduced intracellular VZV yields less than 2-fold compared to those of untreated cells. Since the levels of IFN-␥ in the supernatant were reduced by VZV infection in both ARPE-19 and MeWo cells compared to those of uninfected cells, and were less than 10 pg/ml (40), IFN-␥ produced in response to VZV infection is not sufficient to inhibit VZV replication.…”
Section: Discussionmentioning
confidence: 93%
“…A cytokine profile of ARPE-19 and MeWo cells in response to VZV (ROka strain) infection showed that VZV-infected ARPE-19 cells secreted high levels of CCL2/monocyte chemoattractant protein 1 (MCP-1), CXCL8/interleukin 8 (IL-8), IL-6, and IL-10 and low levels of IL-2, IL-4, IL-13, and tumor necrosis factor alpha (TNF-␣) (40). The only cytokine induced by VZV infection in MeWo cells was IL-10 (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was of great interest to us because recent evidence points to IL-6 as a keystone immunomodulatory cytokine in both healthy and diseased tissues, including a related report about cultured human retinal cells [16]. …”
mentioning
confidence: 99%
“…ARN and posterior uveitis represent severe intraocular infections that may be complicated by: retinal detachment, occlusive vasculitis, and loss of vision. VZV infection is the commonest cause of both of these eye in lammatory disorders [411,412]. Studies have shown that the following cytokines are signi icantly elevated during ARN: IL-6, IL-8, IL-10, IL-18, IL-15, MIF, MCP-1, Eotoxin, IP10, sICAM-1, and sVCAM-1 and their levels correlate with disease activity, while low levels of the following cytokines have been encountered: IL-2, IL-4, IL-13, and IFN-α [411,412].…”
Section: Role Of Cytokines In Vzv Infectionsmentioning
confidence: 99%